Analysis of the Effect of Artificial Intelligence on Role Cognition in the Education System - Jianjian Zhu; Chuming Ren (Occupational Therapy International)
Taking the entire education system in Taiyuan City, Shanxi Province, Central China, as an example, this paper uses the questionnaire survey method to analyze the effect of artificial intelligence (AI) on role cognition in the education system. The education system targeted by this questionnaire survey involves 8 categories: preschool education, primary education, secondary education, higher education, adult education, computer network education, enterprise education, and social education; the respondents include 368 teachers, 402 students or learners, 118 school managers, and 124 family members of students or learners in all above education categories. The questionnaire design has a total of 34 question classified into 6 role cognition items, with a 5-level score; a total of 1012 questionnaires were distributed, and 978 were recovered with a recovery rate of 96.64%, in which 957 were valid questionnaires with an effective rate of 97.85%. The study results show that the learning of AI-assisted courses is strongly dependent on course role cognition, and the construction of role cognition is related to the understanding of course content, teaching methods, and activity methods. Therefore, the effect of AI on role cognition in the education system needs to be systematically analyzed from the aspects of function realization form, resource presentation method, supporting hardware form, teacher-student interaction method, and representation method of works. As connecters, teacher’s role cognition is limited by the degree of understanding learners, the amount of resources, and data processing capabilities, but the advantage is that they can flexibly monitor and adjust. AI technology is flexible and diverse, it functions in learning and teaching activities in a variety of ways, and there is no agreement on the terminology to describe its role in role recognition. The results of this paper provide a reference for further researches on the effect of AI on role cognition in the education system.